Meningkatkan Kreativitas Siswa dalam Menganalisis Kebebasan Pers dengan Metode Pemberian Tugas - Hotman Aritonang (Universitas Negeri Medan, 2015)
The subject of this research is 43 persons of students at class of Natural Science-1 grade XII, as the object is Teaching Method of Tasking, with collecting data conducted by using observation list and questionaire. Based on the pre-test to 43 students, shows that 22 students (55.2 percent) obtained lower score of learning result, and only 15 students (34.8 percent) predicated middle level of creativity, and 6 students (14 percent) predicate good level of creativity, and the average score reached is 62.9 percent. In the first cycle, 8 students (18.6 percent) achieved good predicate of creativity, while 22 students (52.5) predicated middle level of creativity, and 13 students (30.2 percent) predicated lower level ofcreativity, by the average score of 65.4 percent. In the second cycle, there is increasing of score by 30 students (69.8 percent) predicated good level of creativity and the achieved average score of 82 percent. By questionaire in the last meeting, there is increasing on 35 students (81.4 percent) predicated good level of creativity and only 3 students (7 percent) predicated lower level of creativity and the obtained average score of 84.9 percent. Based on the research, from the first to second cycle, empirically proved there are increasing of learning result significantly. Therefore, using method of tasking can be elevate creativity of students on the subject of Civic Education in the class of Natural Science-1 grade XII SMA 12 of Medan.